POLYGAMY AND CIVIL MARRIAGE. NORMS OF THE FAMILY CODE AND THE REAL SITUATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Polygamy and civil marriage are real phenomena existing in society. However, there is a significant gap between the law and social practice. Should the legislation be changed or should awareness-raising efforts be strengthened? This issue needs to be brought up for public discussion. In Kyrgyz society, family values have always held a special place. However, in recent years, a number of social and legal problems have arisen in family relationships. One of the most controversial issues is polygamy. What are the negative aspects of polygamy and what problems does it cause?
Keywords: civil marriage, official marriage, gap, social and legal problems, domestic violence, legally vulnerable, legal father.